The Effect of Engklek Traditional Game on Gross Motor Skills of 5-6 Year Old Children at Alif Kindergarten in Serang City: Pengaruh Permainan Tradisional Engklek Terhadap Kemampuan Motorik Kasar Anak Usia 5-6 Tahun Di TKIT Alif Kota Serang - Yusvinah, Yusvinah; Nuryati, Nuryati; Umalihayati, Umalihayati (Madrosatuna: Journal of Islamic Elementary School, 2025)
The background of this study is that children appear to be less physically active and have difficulty performing various basic movements in a balanced manner. This study aims to determine the Effect of Traditional Engklek Games on Gross Motor Skills of Children Aged 5-6 Years at TKIT Alif Serang City. This study applies to an experimental research method with a one-group pretest-posttest design. The objects of this study are students at TKIT Alif Serang City. The object of this study is the effect of traditional Engklek games on the gross motor development of children aged 5-6 years at TKIT Alif Serang City. The population in this study was all students at TKIT Alif Serang City, totaling 12 students. This study applies a saturated sampling technique because all members of the population were taken as samples. The data collection method applied is observation and documentation. The data analysis method uses a paired sample t-test with the support of the SPSS Windows version 26 application. The results of the data analysis from the Paired sample T-Test, so that the Sig. (2-tailed) has a value of 0.000 < 0.05, so H0 is rejected, and Ha is accepted, which indicates that there is a significant influence of the traditional engklek game on the development of children's gross motor skills. Based on data analysis in the experimental class, it was obtained that r count > r table = 0.576, so the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. It can be concluded that the traditional engklek game has a positive impact on the development of gross motor skills in children aged 5-6 years at TKIT Alif, Serang City.